Analisis Pengelolaan Keuangan Desa - Elkarya Gulo; Dina Arfianti; Yonson Pane (lppm.eka-prasetya.ac.id, 2020)
The purpose of this study is to determine and analyze the suitability of village financial management and the principles of village financial management in Hiliwalo'o-I Village, Mandrehe District, West Nias Regency with Permendagri No. 133 of 2014. This type of the study is a case study by using a qualitative descriptive analysis approach. Data are collected by doing questionnaires, interviews, and documentation techniques. This study is conducted in Hiliwalo'o-I Village, Mandrehe District, West Nias Regency. The object of this study is the management of village finances in Hiliwalo'o-I Village. The findings indicate that the financial management of hiliwalo'o-I villages started from planning to village financial accountability and the principle of village financial management in Hiliwalo'o-I village have been in accordance with Permendagri No. 113 of 2014.